Sensitivity and Specificity of the Toe‐Brachial Index for Detecting Peripheral Arterial Disease: Initial Findings. (25th August 2015) - Tehan, Peta; Bray, Alan; Keech, Ruth; Rounsley, Richard; Carruthers, Angela; Chuter, Vivienne Helaine
Abstract : Objectives: The toe‐brachial index (TBI) is an alternative to the ankle‐brachial index (ABI) in screening for peripheral arterial disease (PAD); however, there is limited evidence comparing their diagnostic accuracy. This study compared the diagnostic accuracy of the ABI and TBI in a population at risk of PAD. Methods: The sensitivity and specificity of the ABI and TBI were determined by color duplex sonography. Receiver operating characteristic (ROC) analysis was performed. Results: A total of 119 participants were recruited (75 male and 44 female). The sensitivity for PAD was highest for the TBI (71%; ABI, 45%), and the specificity was highest for the ABI (93%; TBI, 78%). Receiver operating characteristic analysis indicated that the TBI (ROC area, 0.77; P = .0001) had greater clinical efficacy for diagnosis of PAD than the ABI (ROC area, 0.65; P = .005). Conclusions: In specific populations, the TBI may have greater clinical efficacy than the ABI for diagnosis of PAD.